Ham, beef and chicken substitutes on the market - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1987)
Quorn is the trade name of an edible fungus: mycoprotein. This new protein-rich food developed in the UK can be made to taste like beef, chicken or ham. Although it is not a product of the latest biotechniques and does not involve genetic...